REVIEW OF CRIMINAL LAW ON THE CONSUMPTION OF FOOD AND DRUG CONTAINING NARCOTICS AND PSYCHOTROPICS (ANALYSIS OF DECISION NO. 17 K/MIL/2016) - Koto, Ismail (International Proceeding of Law and Economic; 2020: International Proceeding of Law and Economic, 2021)
The act of consuming food and drugs containing narcotics and psychotropic substances is very dangerous for health. There are several kinds of dangers caused by consuming narcotics and the users or users of drugs themselves mostly do not know which organs are the effects of consuming drugs. With the regulation of the problem of consuming food and drugs that contain Nakotika and Psychotropic, both in the Criminal Code and Law No. 35 of 2009 concerning Narcotics and also Law No. 5 of 1997 concerning Psychotropics including Presidential Regulation No. 80 of 2017 concerning BPOM. The purpose of this study was to determine the legal arrangements for food and medicine, the legal arrangements for consuming and the study of criminal law for acts. This research is a normative legal research, the nature of a descriptive study that uses secondary data sources that consist of primary, secondary and tertiary legal materials as well as data collection through literature studies as outlined in the form of qualitative analysis. Acts can be convicted if the elements of the criminal act have been fulfilled. All elements of the crime described below constitute a unity. Anyone who commits a criminal offense is threatened with a criminal offense. However, this does not mean that each person who commits the act must be convicted. So that in the future actions such as this case will create deterrence effects for members of the TNI. Acts can be convicted if the elements of the criminal act have been fulfilled. All elements of the crime described below constitute a unity. Anyone who commits a criminal offense is threatened with a criminal offense. However, this does not mean that each person who commits the act must be convicted. So that in the future actions such as this case will create deterrence effects for members of the TNI. Acts can be convicted if the elements of the criminal act have been fulfilled. All elements of the crime described below constitute a unity. Anyone who commits a criminal offense is threatened with a criminal offense. However, this does not mean that each person who commits the act must be convicted. So that in the future actions such as this case will create deterrence effects for members of the TNI.